Strategi Quick Reading dan Deep Reading Mahasiswa Semester Dua dalam Menghadapi Beban Tugas Perkuliahan - Ella Safitri; Irma Wakhidatun Nisa; Wanni Oktavia Pardede; Iswara Mutiara Laksmi; Nisaus Sya'diyah; Trinil Dwi Turistiani (Dharma Acariya Nusantara Jurnal Pendidikan Bahasa dan Budaya, 2026)
Changes in student learning patterns in higher education are influenced by the high intensity of academic assignments and limited study time. These conditions encourage students to use more practical and efficient reading strategies, such as quick reading, rather than deep reading, which requires deeper cognitive engagement. This study aims to analyze the reading strategy tendencies of second-semester students in dealing with the burden of college assignments. The study used a descriptive quantitative approach with a Likert-scale questionnaire as the data collection technique. The results show that students more often use quick reading when facing assignment deadlines and limited academic time because it is considered to help obtain information quickly. However, this strategy can lead to a decrease in in-depth understanding of the content of academic reading. Meanwhile, deep reading is still used on material considered important, complex, or directly related to learning evaluation. This study shows a shift in student reading culture towards more strategic and efficient patterns, which can serve as evaluation material for higher education in building an academic literacy culture that balances reading efficiency and quality of comprehension.